SOSIALISASI PENTINGNYA MINAT BACA UNTUK MENINGKATKAN KUALITAS LITERASI MASYARAKAT DESA - Octarina, Sisca; Hanum, Laila; Puspita, Fitri Maya; Indrawati, Indrawati; Yuliza, Evi; Bangun, Putra BJ (Jurnal Pepadu, 2024)
The awareness of the importance of reading in Indonesia, especially in rural areas, still needs to improve. Rural communities need to understand the importance and benefits of reading. Along with the times, people and even children prefer to use gadgets for entertainment, listening while watching, and other entertainment activities. This activity aimed to enhance the importance of reading interest in rural communities, foster critical thinking and analytical abilities, and improve literacy within the village. The methods employed in this activity included presentations, discussions, question-and-answer sessions, and simulations. The service activity team delivered a presentation on the benefits of reading, an explanation of reading sources, and techniques to enhance interest in reading. Furthermore, a discussion session was held between the service activity team and participants to ascertain the extent of their understanding. The outcome of this activity was to advise children and students to engage in 15 minutes of non-lesson reading before the commencement of the lesson. This program was implemented to foster students’ interest in reading and improve their reading skills. This activity identified new avenues for promoting interest in reading, including the procurement of reading books in schools that must be updated according to the times, educators who innovate, increasing educators’ competence, and expanding the library collection. Utilizing the reading corner to increase interest in reading, it needs to be supported by all parties. The results of the analysis indicate that the literacy movement’s impact can increase interest in reading. Therefore, the results of this activity can be recommended for the school literacy movement to improve students’ interest in reading.